Correlação anatomicofuncional por tomografia computadorizada em inspiração e expiração na tuberculose pulmonar sequelar: estudo transversal - Damian, Michelle Godoy Canazza (2018)
Background: Although many patients with cured pulmonary tuberculosis (PTB) remain with anatomical sequels, the literature lacks of studies that accurately characterize and correlate them with associated dysfunction. The aim of the present study is to correlate anatomical sequels with dysfunctions using two different imaging methods, and to investigate expiration air trapping in post-PTB. Methods: A cross-sectional study comprising 56 cured-PTB patients was performed on clinical evaluation, spirometry, 6-minute walk test, chest x-ray, and inspiratory and expiratory high resolution computed tomography (HRCT). Image exams were reviewed by two radiologists, who scored to disease extension (radiographic and inspiratory scores), and air trapping extension (expiratory score). A tomographic score was also developed, by adding inspiratory and expiratory scores. Intra-class correlation coefficient (ICC) assessed inter-observer reliability while multiple linear regression verified associations of post-bronchodilator spirometric variables and imaginological scores. Results: Majority of participants showed anatomical (98%) and functional (69%) abnormalities, with predominance of obstructive dysfunction (57%). At HRCT, there were irregular opacities with architectural distortion in 98% of participants, bronchiectasis in 84% and emphysematous changes in 21%. After adjustment for control variables, imaging scores were independently associated with post-bronchodilator spirometric variables. While comparing with radiography, HRCT showed stronger association with spirometric values, higher ICCs and demonstrated air trapped in large extension of participants’ lung parenchyma, often not related with emphysematous changes. Conclusion: Chest HRCT predicted dysfunction degree more accurately than radiography, showing large extension of air trapping in the participants’ lungs and suggesting involvement of small distal airways in etiology of airflow obstruction post-PTB.